Development of Electrical Capacitance Tomography for Two Phase Characterization - Shahrin, Muhammad Fahmi (2018)
Electrical Capacitance Tomography (ECT) has caught an attention for researchers and engineers to investigate in detail due to its nature of non-invasive, fast response and low cost depending on some application. Its main objective is to monitor a two phase flow in static and dynamic states as it is essential in industrial processes such as in oil & gas industry. ECT is a method to visualize the information regarding on the distribution of a closed pipe by measuring variations of its dielectric properties internally. This paper presents an improvised method mainly focusing on the two plane of capacitance measurement circuit and also setup installation of the rig. For this project, the author implemented an inner pipe diameter of 5cm, outer pipe diameter of 2cm, electrode width of 1.2cm, electrode length of 14cm and the space between two electrodes is 0.7cm. For measurement purpose, the author used a software called ECTGUI to measure the voltage and capacitance for the variance in two phase flow and an image of permittivity distribution can be obtained from the measurements. In this project, the non-conductive material used to flow inside the pipe are plastic beads, water and oil. By implying this material to be utilized, a visualization of a cross-sectional image for the flow can be monitored in static and dynamic states for further improvement or prevention.